Playing Victim dan Manipulasi Kebenaran: Analisis Teologis dalam Pembacaan Reflektif Kejadian 3:1-24 - Andreas Sese Sunarko; Yonatan Alex Arifianto (Sekolah Tinggi Teologi Baptis, Jakarta, 2023)
Playing victim behavior is the action of those who blame themselves on others and position themselves as victims. This contradictory sense of responsibility is widespread in everyday life. Therefore, this article aims to provide a new understanding and paradigm regarding playing victims that contradicts God's truth.Using descriptive qualitative methods, it can be concluded that playing victims in manipulating the truth is a theological reflection in reading Genesis 3:1-24; first, Christianity must understand the nature of playing victims and its impacts. Genesis 3:1-24 shows how humans blame others or circumstances to avoid responsibility for their mistakes. This also emphasizes the importance of playing the victim in theological ethics and Christian faith. Theological reflection, humility, and an attitude of responsibility in honesty through recognizing mistakes and confessing sins are not to play the victim. Jesus also taught us to live in love. Furthermore, in a theological reflective context, it helps identify the role of the Garden of Eden story and the issue of truth manipulation in the